EFFECT OF CURRENT RATIO, DEBT OF EQUITY RATIO, RETURN ON ASSETS, EARNINGS PER SHARE, AND NET PROFIT MARGIN ON STOCK PRICE IN TRANSPORTATION AND LOGISTICS SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2014-2019 - Hidayat, Afifah Fasya Putri; Ginting, Regita Isabella BR; Adistira, Raufia; Siregar, Della Krisda; Febriany, Syaharany Cantika; Nursjanti, Farida (CENTRAL ASIA AND THE CAUCASUS, 2022)
The financial performance of Indonesian transportation and logistics firms has fluctuated, with the majority of them experiencing a fall in performance during the Covid-19 pandemic. The drop in performance has an effect on the drop in stock prices. The goal of this study is to examine at how the variables Current Ratio (CR), Debt to Equity Ratio (DER), Return On Asset (ROA), Earning Per Share (EPS), and Net Profit Margin (NPM) affect stock prices in transportation and logistics companies listed on the Indonesia Stock Exchange from 2014 to 2019. The results of panel data regression analysis revealed that the CR, DER, and ROA had no significant effect on stock prices. The EPS and NPM are two more variables that have a considerable impact on stock values. The CR, DER, ROA, EPS, and NPM variables have a major impact on stock prices simultaneously.